The Effect of Current Ratio, Debt to Equity Ratio, and Total Asset Turnover on Profit Growth in the Technology Sector - Monik Megasetya; Diah Febriyanti; Kartika Berliani (Cattleya Darmaya Fortuna, 2026)
This quantitative study analyzes the impact of the Current Ratio (CR), Total Asset Turnover (TATO), and Debt-to-Equity Ratio (DER) on the profit growth of technology sector companies listed on the Indonesia Stock Exchange (IDX). Employing a purposive sampling method, the study utilized six secondary financial statement observations, which were analyzed using multiple linear regression following the fulfillment of classical assumption tests. Partial test results indicate that the DER has a positive and significant effect on profit growth, whereas the CR and TATO do not have a significant effect. However, the three variables collectively exert a significant influence. These findings suggest that capital structure is a primary driver of profit. Consequently, management is advised to optimize capital structure management and integrate various financial ratios to maintain the company's stability and performance.